Title IX and Career Pathways of Coaches Across NCAA Women's Basketball Programs: An Intersectional Approach to Human Capital in Hiring - Stephanie Gerretsen; Tarlan Chahardovali; Scott Brooks (University of Kansas Libraries, 2023)
The purpose of this article is to examine the career pathways of NCAA women basketball coaches after the passage of Title IX, with a special attention to the relationship between human capital (i.e., job related qualifications), race, and gender of coaches in the sample population. As such, we looked at job related qualifications of incoming and outgoing coaching hires from 1984-2020 at universities within the Power Five Conferences and HBCUs at the Division I level, considering nine different variables. These variables include a coach's immediate previous position, number of years as an NCAA coach, years of overall coaching experience prior to hire, highest prior division coached, NCAA championship win as a coach, NCAA championship win as a player, highest level of play, highest division played as an athlete, and highest educational degree. Regarding the overall impact of Title IX on women head coaching opportunities, our data shows relatively consistent opportunities for female coaches across the Power Five Conferences and Division I HBCU schools since 1984. Although the opportunities for women were consistent, they do not seem equitable at the Power Five level when considering a coach's race as Black women were hired at a much smaller rate compared to their White counterparts. Our data also shows that despite more women being hired overall, on average, women have greater qualifications as NCAA women's basketball coaches compared to male coaches. This finding shows that women need more human capital than men to obtain head coaching positions which marks the presence of gender discrimination in the NCAA coaching labor market.